Criteria for Evaluating The Quality of a Question Paper - N Shukla, Ajit Kumar (Journal of Technical Education and Training, 2011)
The quality of engineering education is directly the outcome of knowledge implanted and evaluated through formal examination. But there is no such method to evaluate the quality of evaluation through the question paper. This paper proposes the method of such evaluation and present result based on examining few of the question papers. The method so developed can be expanded as per the perception and uniform code of quality can be awarded. The ICTNOS (I see T nos) can be uniformly accepted as the qualitative criteria for the awarding the rating to a question paper.